PENGEMBANGAN POTENSI KOPI SEBAGAI KOMODITAS UNGGULAN KAWASAN AGROPOLITAN KABUPATEN DAIRI - Jujur T N Sitanggang (Departemen Ekonomi Pembangunan USU, 2013)
Coffee is a leading commodity of Dairi Regency but the potential has not been digged optimally. The presence of development programs of The Dairi Regency Agropolitan Area (KAKD) open a new hope to improve the development potential of the Dairi Regency coffee the most. The data used in this research is the primary and secondary data. Identification and analysis results of the research showed that Dairi Regency is a highly potential areas in the development of Coffee because there is a lot of excellence which is not possessed in other areas such as: Agroklimat that is appropriate for the coffee plant, the experienced coffee farmers and many more. The methods used to find the exact strategy is a SWOT analysis method. The comprehensive strategies that is found as the result of SWOT analysis method is as follows : (1) The formation of Coffee Research and Development Institution; (2) Government role improvement; (3) The formation of The Coffee Farmers Association DairiRegency ; (4) The implementation of the concept of The Dairi Regency Agropolitan Development in Coffee County Dairi.